Artificial Intelligence sebagai Media Pembinaan Rohani Jemaat: Analisis Kuantitatif pada Gereja Baptis Indonesia Bogor - Julio Warmansyah; Johanes Suharso (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The rapid development of Artificial Intelligence (AI) has created new opportunities for church ministry, particularly as a medium for congregational spiritual formation. However, empirical evidence regarding its effectiveness in enhancing spiritual awareness remains limited, especially within the context of local churches in Indonesia. This study aims to examine the influence of digital literacy, participation in church-based digital technology training, the frequency of AI application use for spiritual activities, perceptions of AI effectiveness, and church leadership support on congregational spiritual awareness. A quantitative survey was conducted involving 140 young adult members of the Indonesian Baptist Church of Bogor selected through purposive sampling. Data were analyzed using multiple linear regression. The results indicate that the five independent variables collectively contribute to spiritual awareness, explaining 84.3% of the variance. Nevertheless, only church leadership support has a statistically significant partial effect on spiritual awareness, whereas digital literacy, digital technology training, AI usage, and perceptions of AI effectiveness do not show significant individual effects. These findings suggest that AI functions primarily as a supporting medium for spiritual formation, while its effectiveness depends largely on church leadership in directing its use according to biblical values and the spiritual development of the congregation. This study provides practical implications for churches in designing digital ministry strategies that integrate technological innovation with Christ-centered spiritual formation..